Harmonization Of Procedure: Changes In The Composition Of Shareholders In Limited Liability Company - Christino Deseka (Journal of Law and Policy Transformation, 2024)
A limited liability company is one of the legal entities in recognized in Indonesia. As a legal entity, limited liability company will continue to exist even if there are changes in its shareholders.  When there are changes in the composition of company’s shareholders, it must be notified/reported to the Minister of Law and Human Rights to be listed in the Company Register. If such notification has not been carried out, according to the prevailing provision, the Minister will reject any application for approval or notification based on the composition or names of shareholders who have not been notified.  Regarding the reporting to the Minister regarding the changes of the composition of company’s shareholders, it is regulated in UUPT and Permenkumham 21/2021. This study analyzes the consistency of both regulation in regulating the procedure in reporting the changes in the composition of company’s shareholders within limited liability companies to the Minister. This research used normative legal research. The results of the research show that there are significant difference in reporting procedure, which may lead to various legal and implementation issues. These findings suggest the need to revise existing regulations to ensure consistency, clarity and legal certainty in reporting changes in shareholder composition in Indonesian companies.